FRONTAL PLANE ANALYSIS AT KNEE IN TRANSTIBIAL AMPUTATION - PURNIMA SHRIVASTAVA; KAREN PAVRI (International Journal of Pharma and Bio Sciences, 2015)
To study and compare frontal plane kinetics and kinematics at knee joint during the gait cycle in persons with transtibial amputation using Patellar tendon bearing (PTB) suprapatellar (SP) cuff suspension and PTB supracondylar (SC) suspension, with SACH foot. Instrumented gait analysis was performed in 30 persons having unilateral transtibial amputation of traumatic origin using either PTB prosthesis with SP cuff suspension or SC suspension with SACH foot. The reports obtained were used for statistical analysis by using student’s unpaired t-test with CI 95% and p-value <0.05 and, by percentage comparison.Statistically significant differences were found in knee excursion at mid stance (p= 0.02) , 47% of persons using PTB SC suspension have shown abnormal varus moment at knee at mid stance in frontal plane. Whereas 80% of persons of both group have shown abnormal power generation at knee at weight acceptance.This study identified abnormality in frontal plane knee excursion and knee moment in PTB-SC group which may be due to interface used in PTB-SC socket designs.